Structured Feedback Training for Time-Out: Efficacy and Efficiency in Comparison to a Didactic Method. Issue 5 (September 2018) - Jensen, Scott A.; Blumberg, Sean; Browning, Megan
Although time-out has been demonstrated to be effective across multiple settings, little research exists on effective methods for training others to implement time-out. The present set of studies is an exploratory analysis of a structured feedback method for training time-out using repeated role-plays. The three studies examined (a) a between-subjects comparison to more a traditional didactic/video modeling method of time-out training, (b) a within-subjects comparison to traditional didactic/video modeling training for another skill, and (c) the impact of structured feedback training on in-home time-out implementation. Though findings are only preliminary and more research is needed, the structured feedback method appears across studies to be an efficient, effective method that demonstrates good maintenance of skill up to 3 months post training. Findings suggest, though do not confirm, a benefit of the structured feedback method over a more traditional didactic/video training model. Implications and further research on the method are discussed.